Sujecion de piezas durante las mediciones con M.M.C - Miguel Ángel Sellés Cantó; Elena Pérez Bernabéu; Victor Gisbert Soler (3C Tecnología, 2012)
This Coordinate Measuring Machines (C.M.M.) has had an increasingly important role throughout history. We are talking to an enterprise-level quality control. A system that is being implemented in all companies, and has developed some tools to control a variety of parameters such as production stabilization.In this paper, we first set out an introduction to the use of C.M.M. as tools for quality control in SME's. Then we explore the importance of piece positioning and clamping before being measured in a C.M.M. We finally analyze four possible moorings, and deviations are obtained. These moorings are designed in order to place the same work piece in the four cases.Finally, the results obtained are compared and show which is the best way to put the part on the C.M.M.